Pengaruh BErita Online Clickbait Terhadap Minat Baca Peserta Didik SMKN 1 Kersana - Wahyu Dianto; Hany Uswatun Nisa; Prasetyo Yuli Kurniawan (Jurnal Ilmiah Wahana Pendidikan, 2022)
Along with the development of the news era appears in various forms, one of which is online news . In some online news has its own character is to use clickbait . Clickbait often makes readers deceived about the headlines they read. But on the other hand clickbait on online news can also provide an increase in reading interest and train readers to think critically to look for evidence of clickbait online news . This study was attempted to identify how the influence of clickbait online news on the reading interest of the students of SMKN 1 Kersana. This research uses quantitative research methods and the concept of correlation research with and using techniques random sampling with a sample size of 70. Data collection was tried with a questionnaire. The data analysis method uses the normality test, the linearity test which is tried as a prerequisite for the analysis, and the t-test to test the hypothesis. The results of this study prove that there is an influence between clickbait online news headlines on the progress of reading interest based on the results of the t test the results obtained t count : 2, 195, that 2, 195 > 1.667. So the bond in this research is that there is an influence of clickbait online news on the progress of reading interest in students of SMKN 1 Kersana.